In-vitro Plant Regeneration from Protoplast in Brassica Family - Pongrat, Ariyaporn (Agriculture and Natural Resources, 1998)
Nine species of Brassica family were studied for the genetic control of in vitro regenerability from protoplast. In Brassica family, the protoplast culture should be kept in the dark after the protoplast isolation for the first three days to reduce the phenols as they affected cell division and growth of cells during the culture. The callus formation did not depend on the genotype since the protoplasts of all examined species showed a high microcallus and callus formation in V-KM and on MS-media, respectively. The protoplast regeneration of Brassicaceae was strongly dependent on the genotype. The examined species with the Agenome, namely Brassica campestris (AA), B. juncea (AABB) and B. napus (AACC) showed low capability of regeneration. Probably, the A-genome has an inhibitory effect on the regeneration in Brassica species. The genomes of B. nigra (BB) and B. oleracea (CC) had high frequency of protoplast regeneration. Their interaction enhanced the ability to regenerate since B. carinata (BBCC) showed the best regenerability from protoplasts. Moreover, Erucia sativa, Raphanus sativus and Sinapis alba could not form shoot from protoplasts.